The Role of Employee Engagement Mediates the Influence of Quality of Work Life on Employee Performance - Kusuma, Angela (Jurnal Manajemen, 2021)
Professional human resources who are highly dedicated to the organization have a strategic role and are one of the key factors in the success of an organization to achieve the predetermined vision or target. Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities assigned to him. The performance achieved by a company is basically the achievement of the members of the company itself, starting from the executive level to operational employees. The purpose of this study is to analyze the role of employee engagement to mediate the influence of quality of work life on employee performance at the Bank Indonesia Representative Office, Bali Province. The number of samples used are 66 employees using the saturated sample method. Data were analyzed using path analysis techniques and was collected through questionnaires. The results indicate that the quality of work life has a positive and significant effect on employee performance, employee engagement has a positive and significant effect on employee performance, the quality of work life has a positive and significant effect on employee engagement, and Employee engagement positively and significantly mediates the influence of quality of work life on employee performance.